1968
DOI: 10.1128/aem.16.10.1457-1459.1968
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Homocarnosine and Other Compounds Against Staphylococcal Infections in Mice

Abstract: Homocarnosine and carnosine have been identified in bovine brain extracts which are effective in protecting mice against infections by Staphylococcus aureus. These peptides, as well as L-histidine, L-1-methylhistidine, f-alanine, y-aminobutyric acid, 6-aminovaleric acid, E-aminocaproic acid, 1-aminomethylcyclohexane-4-carboxylic acid, and anserine, were tested as prophylactic agents against S. aureus infections in C3H and Swiss mice. Histidine and methylhistidine were ineffective in preventing mortality in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1969
1969
1971
1971

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Peptide and its component amino acids. Previous work (15) showed that whereas homocarnosine protected animals against infections, its components, L-histidine and y-aminobutyric acid, by themselves were ineffective in Swiss mice with the dosage schedule used. Therefore experiments were undertaken to determine (i) the effect of a mixture of the two component amino acids in equimolar concentrations and (ii) the effect of a combination of homocarnosine with any one of the components.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peptide and its component amino acids. Previous work (15) showed that whereas homocarnosine protected animals against infections, its components, L-histidine and y-aminobutyric acid, by themselves were ineffective in Swiss mice with the dosage schedule used. Therefore experiments were undertaken to determine (i) the effect of a mixture of the two component amino acids in equimolar concentrations and (ii) the effect of a combination of homocarnosine with any one of the components.…”
Section: Resultsmentioning
confidence: 99%
“…Although the physiological function of homocarnosine is still speculative, the present studies have shown its ability to induce resistance to staphylococcal infections in mice. Tanaka et al (15,16) reported that the dipeptides, L-carnosine, homocarnosine and anserine, possess antistaphylococcal properties in C3H mice and proposed that the protective value of brain extract may in part be ascribed to these peptides or compounds related to them. Although we confirmed the antistaphylococcal property of homocarnosine, we did not find such activity for carnosine or anserine in Swiss albino mice, except perhaps in the early stages of infection, under the conditions of assay (15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…p. 283, 1964. Further studies with the amino acid analyzer and an Amberlite CG-120, 2,6-lutidine column followed by a diazo-coupling reaction confirmed the presence of carnosine and homocarnosine in the bovine extract (11,12).…”
mentioning
confidence: 88%